Variability in volatile composition of Skimmia anquetilia N.P. Taylor & Airyshaw. Issue 4 (4th July 2017) - Chauhan, Rajendra S.; Nautiyal, M.C.; Dhyani, A.; Bahuguna, Y. M.; Rawat, Sanskrita; Tava, Aldo; Cecotti, R.
Abstract: This work was aimed to analyze the composition of the volatile oil of Skimmia anquetilia (syn. S. laureola, Rutaceae), an medicinal and aromatic shrub growing in the temperate zone along Central and Eastern Asia. Samples were collected during flowering phenophase, and fresh leaves used for the extraction of volatile oil by using a Clevenger-type apparatus till three and a half h. The process yielded a total of 28 compounds, which were identified using GC-FID and GC/MS analysis. Major constituent of the volatile oil was linalyl acetate (35.0 %), whereas other abundant components were β-phellandrene (18.3 %), linalool (15.6 %), pregeijerene (11.9 %), α-terpineol (3.95 %), geijerene (1.16 %), geranyl acetate (1.68 %). Comparisons with previous studies revealed a great variability in the composition of this essential oil. Further studies ought to be extended to the identification of chemotypes, ecotypes or chemical races for genetic improvement of S. anquetilia. This species has a good economic potential as its essential oil is commercially valuable in the flavour and fragrance industry.